Between “Koto” & “Hablu Min Nan Nas” - The perceptions of intercultural environmental education in local gardens: a preliminary study on selected Japanese gardens design around Kyoto City, Japan - Mohd. Yaman, Maheran; Kawasaki, Masashi (Common Ground Publishing Pty Ltd, 2008)
There are two types of garden in this study. One type is the gardens which, are designed for strolling and observing. Examples of them are the Tenryu-ji garden (Figure 1) and the Ryoan-ji (Figure 2) gardens. Both are World Cultural Heritage sites (Kubota & Oshima, 2007). These are examples of garden in temples or worshiping public area. The second type is gardens for royalty such as Katsura. Every angle of areas in Katsura garden (Figures 3 & 4) gives different views. The four seasonal changes add to the dramatic effect of colours in the picturesque frame (Kawasaki & Yamaguchi, 2007). This kind of garden is a mixed of both as described earlier. The overall intentions for all the gardens examples above are for meditation or learning from the environment. Thus, explains the Japanese notion of koto which is similar to the concept of hablu min nan nas (relation of human and environment). In Islam, it can be a useful concept to explain on environmental link with education.